Royal Jelly and Fermented Soy Extracts—A Holistic Approach to Menopausal Symptoms That Increase the Quality of Life in Preand Post-menopausalWomen: An Observational Study - Balan Andreea; Moga Marius Alexandru; Neculau Andrea Elena; Mitrica Maria; Rogozea Liliana; Ifteni Petru; Dima Lorena (Nutrients, 2024)
Background: The objective of this study was to determine the effects of royal jelly and fermented soy extracts on menopausal symptoms and on quality of life in pre- and post-menopausal women. Materials and method: This prospective observational study was carried out in a Clinical Hospital of Brasov, Romania, during June 2020 and December 2021. Eighty pre- and post-menopausal women, aged between 45 and 60 years, were included in two groups. The first group (40 women) received a dietary supplement with fermented soy extract twice a day for eight weeks and the second group (40 women) received the same dietary supplement with fermented soy extracts and 1500 mg of royal jelly capsules for eight weeks. After the treatment, the MENQOL score, DASS-21 score, and the mean number and intensity of daily hot flushes were recorded and compared with baseline values. Results: After eight weeks of treatment, the score of the MENQOL questionnaire and all its domains’ scores decreased in comparison with the baseline in both groups (p < 0.001). Also, the DASS-21 score (p < 0.001), depression score (p < 0.001), anxiety score (p < 0.001), and stress score (p < 0.001) improved. The mean number and the intensity of hot flushes decreased in both groups (p < 0.001). Comparing these variables after the treatment in both groups, we observed that the women who received dietary supplements with fermented soy extracts and royal jelly capsules recorded better scores for MENQOL (vasomotor, physical, and psychosocial domains) and a more reduced mean number of daily hot flushes. Conclusions: This observational study suggests that both dietary fermented soy supplements and royal jelly capsules possess beneficial effects against menopausal symptoms, increase the quality of life in pre- and post-menopausal women, and that the effects might be significantly improved if those dietary supplements are administered in association.
Keywords: royal jelly; menopause; fermented soy extracts; vasomotor symptoms